Dificuldades de aprendizagem em cálculo e a relação com raciocínio lógico formal: uma análise no ensino superior - Donel, Marlene Lucia Holz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research, with a qualitative and quantitative approach, was characterized by a case study that had, as a main goal, to analyze the relations between the cognitive development and the learning difficulties in the discipline of Integral Differential Calculus, in academics of a Federal Public University of Paraná. The discussion was based in the Constructive Theory of Piaget, focused on the comprehension of the construction process and learning of Mathematics. Its application was performed in three steps, involving first term Engineering academics, freshmen between 2011 to 2014.The first step consisted in the Analysis of the Academic Performance in the discipline Integral Differential Calculus of the freshmen in the Engineering courses, between 2011 to 2013, that showed a general average of 55,7% of failing in the mentioned discipline. The second step focused on the Evaluation of the Mathematics Contents of the freshmen academics in Engineering in the second term of 2013. The instrument of this second step of evaluation was elaborated by expert teachers in the mathematics area and aimed to verify the domain of the mathematics contents learned in previous stages of learning, necessary to the understanding of the contents provided for the discipline Integral Differential Calculus. This application was performed in two moments, with distinct purposes. From this last one, it was selected a sample of the applied instrument of 21 flunked participants in the Discipline of Integral Differential Calculus to perform the correction and attribution of a concept (grade).The results of this stage indicated that, 85% of the academics do not show domain of the concepts and the mathematics basic notions required to the good performance in the mathematics discipline. The third and last step of the research was directed to academics of the Engineering of Nourishment, because it was pointed as the course with the biggest index of reproofs and...

Esta pesquisa, de abordagem qualitativa e quantitativa, caracterizou-se por um estudo de caso que teve como principal objetivo analisar as relações entre o desenvolvimento cognitivo e as dificuldades de aprendizagem na disciplina de Cálculo Diferencial Integral, em acadêmicos de uma Universidade Pública Federal do Paraná. A discussão apoiou-se na teoria construtivista piagetiana, voltada à compreensão do processo de construção e aprendizagem da matemática. Sua aplicação foi realizada em três etapas, envolvendo acadêmicos do 1º período de Engenharia ingressantes entre os anos de 2011 a 2014. A primeira etapa consistiu na Análise do Rendimento Acadêmico na disciplina de Cálculo Diferencial Integral de ingressantes nos cursos de Engenharia entre os anos de 2011 a 2013, que mostrou uma média geral de 55,7% de reprovação na referida disciplina. A segunda etapa voltou-se para a Avaliação do Conteúdo Matemático dos acadêmicos ingressantes na Engenharia no 2º Sem/2013. O instrumento utilizado nessa etapa foi elaborado por professores especialistas na área da matemática e visava verificar o domínio dos conteúdos matemáticos apreendidos em graus anteriores de ensino, necessários ao entendimento dos conteúdos previstos para a disciplina de Cálculo Diferencial Integral. Essa aplicação foi realizada em dois momentos, com finalidades distintas, sendo que desta última foi selecionada uma amostra do instrumento aplicado, de 21 participantes reprovados na Disciplina de Cálculo Diferencial Integral para realização da correção e atribuição de um conceito (nota). Os resultados dessa fase indicaram que, 85% dos acadêmicos não demonstram domínio de conceitos e noções básicas da matemática necessários ao bom desempenho na disciplina de matemática. A terceira e última etapa da pesquisa, foi direcionada a acadêmicos da Engenharia de Alimentos, por ter sido apontado como o curso com maior índice de reprovações...
Keywords: Cálculo diferencial; Disturbios da aprendizagem; Ensino superior; Raciocínio; Differential calculus